2000
DOI: 10.1046/j.1365-2141.2000.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Assay discrepancy in mild haemophilia A due to a factor VIII missense mutation (Asn694Ile) in a large Danish family

Abstract: Summary. Factor VIII gene analysis in a large consanguinous Danish family comprising 24 affected males and four homozygously affected females revealed an Asn694Ile mutation within the A2 domain. The factor VIII gene mutation led to a mild haemophilia A phenotype with factor VIII function displaying discordance between one-stage clotting and chromogenic two-stage assays. In one-stage assays, values ranged from 0´05 to 0´30 IU/ml (males) and from 0´19 to 0´29 IU/ml (homozygous affected females), whereas the chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
2
54
0
Order By: Relevance
“…Later on, biochemical analysis of recombinant FVIII carrying the substitution Arg531His indicated that, following activation by thrombin, the mutant FVIII had an accelerated rate of spontaneous inactivation due to an increased rate of dissociation of the A2 subunit [45,46]. This observation suggested a role for Arg531 in stabilizing the activated FVIII molecule.…”
Section: Molecular Mechanisms Of Mild/moderate Hemophilia Amentioning
confidence: 99%
“…Later on, biochemical analysis of recombinant FVIII carrying the substitution Arg531His indicated that, following activation by thrombin, the mutant FVIII had an accelerated rate of spontaneous inactivation due to an increased rate of dissociation of the A2 subunit [45,46]. This observation suggested a role for Arg531 in stabilizing the activated FVIII molecule.…”
Section: Molecular Mechanisms Of Mild/moderate Hemophilia Amentioning
confidence: 99%
“…, 1996; Mazurier et al. , 1997) or Coamatic (Schwaab et al. , 2000) have been used, as well as from Dade (Sysmex, Milton Keynes; Keeling et al.…”
Section: Discussionmentioning
confidence: 99%
“…A family pedigree has been described in which all members have 2-st FVIII activities that are one half of that measured by 1-st assay. 36 This pedigree included affected males as well as homozygous females. Molecular analysis identified a missense mutation at residue 694 within the A2 subunit where ILE is substituted for ASN.…”
Section: Discussionmentioning
confidence: 99%